Reading masques : the English masque and public culture in the seventeenth century - Shohet, Lauren (Oxford : Oxford University Press, 2010)
Considering masques from the point of view of reception as well as production, this work illuminates intersections of elite and public culture in 17th century England. Lauren Shohet traces the ways that both courtly and non-courtly masques circulated, and rethinks what it means to "read" a masque.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Masques, English -- History and criticism; English drama -- 17th century -- History and criticism